Aterosclerose na adolescência: Atherosclerosis in adolescence - Farah de Aguiar, Adolfo Alexandre (Adolescência e Saúde, 2009)
Atherosclerosis is one of the main causes of death in Brazil and in the whole world, mainly in industrialized countries, that disseminate unhealthy habits of life. The diet rich in pasta and fried food and poor in green vegetables and fruits is still used by a great proportion of the population. Adolescents’ habits of fast food, smoking, and keeping back of exercises, being hours using the computer result in a process of lesion to the organism that culminates with true disasters to arterial vases and very high costs. Within 12 years, taking age into account, atherosclerosis will lead even more, followed by respiratory diseases and neoplasias